Access to credit: Awareness and use of formal and informal credit institutions - Alejandra Campero; Karen Kaiser (Banco de México, 2013)
In this paper we study the determinants of use of formal and informal credit sources. Given that awareness is a necessary step towards use of credit, in order to control for the possible selection bias we decompose the decision to use credit as a two stage decision process in which first, households form their choice set by deciding which type of institutions they want to consider as possible lenders (awareness), and then choose among them (use). Additionally, we allow for correlation between being aware of a specific source of credit and using it. We find evidence that supports the hypothesis that the formal and informal credit markets in Mexico attend different segments of the population. However, our results also show that informal lending sources' characteristics are valued per-se by consumers in certain situations, such as emergencies.
Keywords: D1; D14; G2; 330; credit demand; consideration set; informal credit; formal credit; Mexico